The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s13205-018-1527-1
|View full text |Cite
|
Sign up to set email alerts
|

Keratinolytic activity of Bacillus subtilis LFB-FIOCRUZ 1266 enhanced by whole-cell mutagenesis

Abstract: Discarded feathers represent an important residue from the poultry industry and are a rich source of keratin. Bacillus subtilis LFB-FIOCRUZ 1266, previously isolated from industrial poultry wastes, was used in this work and, through random mutation using ethyl methanesulfonate, ten strains were selected based on the size of their degradation halos. The feather degradation was increased to 115% and all selected mutants showed 1.4-to 2.4-fold increase in keratinolytic activity compared to their wild-type counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 59 publications
(68 reference statements)
1
15
0
Order By: Relevance
“…The mutants exhibited higher feather degradation rate by 15% than the wild type strain. In addition, the mutants showed higher keratinolytic activity and sulfide yield than the wild type strain (de Paiva et al, 2018). Mutation using ultraviolet irradiation and N-methyl-N′-nitro-N-nitrosoguanidine treatment or N-methyl-N′-nitro-N-nitrosoguanidine treatment alone was carried out on B. subtilis .…”
Section: Microbial Degradation Of Feathersmentioning
confidence: 94%
“…The mutants exhibited higher feather degradation rate by 15% than the wild type strain. In addition, the mutants showed higher keratinolytic activity and sulfide yield than the wild type strain (de Paiva et al, 2018). Mutation using ultraviolet irradiation and N-methyl-N′-nitro-N-nitrosoguanidine treatment or N-methyl-N′-nitro-N-nitrosoguanidine treatment alone was carried out on B. subtilis .…”
Section: Microbial Degradation Of Feathersmentioning
confidence: 94%
“…Second, a medium for the microorganism growth needs to be set up. As the media for enriching bacteria or fungi are different, a suitable medium is important in the screening (De Azeredo et al, 2006;Fakhfakh et al, 2011;Mazotto et al, 2013;Parrado et al, 2014;Arokiyaraj et al, 2019). In addition, other parameters such as cultural time and temperature should be considered based on the experimental objectives.…”
Section: Keratinase-producing Microorganismsmentioning
confidence: 99%
“…Interestingly, a study showed that glucose and ammonium nitrate are not good sources for growing Stenotrophomonas maltophilia to degrade feathers (Qu et al, 2018). Accumulated studies suggest that different microorganisms require various fermentation conditions for large-scale production, indicating that careful exploratory studies are necessary prior to the large-scale production of the enzymes (Jagadeesan et al, 2020;de Menezes et al, 2021;Deniz et al, 2021;Sharma and Kango, 2021). It was demonstrated that the solidstate fermentation increased keratinase production compared with the commonly used submerged fermentation (Inácio et al, 2018).…”
Section: Microbial Production Of Keratinasesmentioning
confidence: 99%
See 2 more Smart Citations